Alternative learning model in physics learning: Effect of the conceptual change model with cognitive conflict on critical thinking skill - Insih Wilujeng; Zul Hidayatullah (Universitas PGRI Kanjuruhan Malang, 2021)
The purpose of this study was to apply the Conceptual Change Model (CCM) containing cognitive conflicts and to find out the difference in their effects on students' critical thinking skills. This type of research is a quasi-experimental study with an Only-Posttest design. The sample in this study was 91 students at senior high school in Lombok, Indonesia. The sampling technique used in this research is simple random sampling. Students are divided into three sample groups: experiment class, control 1 class, and control 2. Critical thinking skills are measured based on five aspects: basic clarification, basic decisions, inference, evaluation, and further explanation. The test used to measure critical thinking skills is a description test. The material chosen is motion along a straight line. This research was tested by ANOVA 1 way. The test results show differences in the critical thinking skills of the three sample groups in the motion and straight line material. This shows that CCM containing cognitive conflict can be used as alternative learning to improve critical thinking skills. Subsequent research is carried out for different materials and different areas, but it should be noted that this learning is suitable for materials that experience many misconceptions.